Crash: Find the Exit- A neuroscience board game as a tool to discuss mechanisms of drug abuse and addiction issues in the classroom - Da Silva Chagas, Luana; Chagas De Almeida Silva, Sarah; Matos Coelho De Oliveira, Rafaela; Magalhães Manhães, Thaís; Vicenta De Oliveira Braga, Giovanna; Sarmiero Rodolpho, Beatriz; De Souza Pereira, Helena; Oliveira Silva Bomfim, Priscilla (Journal of biological education, 2022)
Discussing substance abuse, licit or not, requires dynamism when it comes to adolescents. Games are a powerful tool to bring the subject up for discussion. Here we describe a collaborative board game designed to address this subject using current neuroscience knowledge about neurophysiology of (drug) addiction. The game highlights the action of 22 neuroactive drugs, classified into the following groups: (1) depressants; (2) hallucinogens; (3) stimulants and (4) others (anabolic steroids and prescription drugs). In addition, the game was developed to approach specific neuroscience-related themes such as: (1) brain structures (e.g. lobes); (2) cell types present in the nervous system; (3) neurotransmitter actions; (4) impact of drug abuse on the nervous system function; (5) the concept of overdose. Moreover, the game has got an educational proposal that combines the individual and social aspects of development, addressing concepts of neurosciences in a playful and stimulating way, aiming to promote not only awareness regarding the abuse of chemical substances, but also to stimulate the social development of the participants at the same time. It is worth mentioning that drug cards also bring curiosities and cultural trivia, including music and art, making it more attractive for young audiences.